2019
DOI: 10.1111/jomf.12627
|View full text |Cite
|
Sign up to set email alerts
|

Nonstandard Work Schedules and Father Involvement Among Resident and Nonresident Fathers

Abstract: Objective The authors examined associations between resident and nonresident fathers' nonstandard work schedules, work hours, and their level of involvement with their young children in the United States. Background Nonstandard work schedules may negatively impact father involvement either directly by reducing fathers' availability or indirectly by taking a toll on their well‐being. Prior research on nonstandard schedules and father involvement has focused on two‐parent households, yet nonstandard schedules ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
(88 reference statements)
4
18
0
Order By: Relevance
“…Consistent with extant research (Pilarz et al, 2019), our results indicated that fathers who work more hours per week report less frequent verbal engagement with their infants. However, fathers’ work hours were surprisingly not related to their caregiving or physical play despite past research demonstrating that fathers’ total work hours were negatively correlated across various forms of father involvement (e.g., accessibility, engagement, and responsibility; Pilarz et al, 2019). Perhaps when low-income fathers have limited time and energy as a result of long work hours, they prioritize some forms of engagement (e.g., physical play and caregiving) over others (e.g., verbal engagement).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with extant research (Pilarz et al, 2019), our results indicated that fathers who work more hours per week report less frequent verbal engagement with their infants. However, fathers’ work hours were surprisingly not related to their caregiving or physical play despite past research demonstrating that fathers’ total work hours were negatively correlated across various forms of father involvement (e.g., accessibility, engagement, and responsibility; Pilarz et al, 2019). Perhaps when low-income fathers have limited time and energy as a result of long work hours, they prioritize some forms of engagement (e.g., physical play and caregiving) over others (e.g., verbal engagement).…”
Section: Discussionsupporting
confidence: 90%
“…Generally, our results suggest that infant age is a salient child characteristic (although not with respect to fathers' caregiving), but it seems paternal engagement is not driven to a large extent by other measured child characteristics within a low-income sample. Consistent with extant research (Pilarz et al, 2019), our results indicated that fathers who work more hours per week report less frequent verbal engagement with their infants. However, fathers' work hours were surprisingly not related to their caregiving or physical play despite past research demonstrating that fathers' total work hours were negatively correlated across various forms of father involvement (e.g., accessibility, engagement, and responsibility; Pilarz et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Nonstandard schedules likewise influence child–parent relationships. Working nonstandard hours generally decreases time spent with children (Hook, 2012; Pilarz, Cuesta, & Drazen, 2020), but such schedules may also allow some men to increase the amount of time they spend with their children (Mills & Täht, 2010). In part, this may be due to “tag‐team parenting” (Täht & Mills, 2012) in which dual‐career parents balance nonstandard hours such that one parent is typically present with the child (ren) (Barnett & Gareis, 2007; Folk & Yi, 1994; Glass, 1998; Nock & Kingston, 1984; Presser, 1988).…”
Section: Family and Domestic Outcomesmentioning
confidence: 99%
“…To address potential biases caused by missing data, we used multiple imputation with chained equations for all the variables in the study (Royston & White, 2011). Considering that some cities do not have weights and that no corresponding weights to address attrition were available in Year 15, we followed other published studies (Parkes et al, 2019; Pilarz et al, 2019; Schroeder et al, 2020) and controlled for variables that were used to create survey weights rather than apply the survey weights to the analyses.…”
Section: Methodsmentioning
confidence: 99%